Simplifying the Multiparty System or Compromising Equality? Legal Challenges and the Current Political Landscape in Indonesia - Muh. Hasrul; Farida Patittingi; Ahsan Yunus (Sriwijaya Law Review, 2025)
Political parties play a vital role in Indonesia’s democratic system, functioning as key platforms for citizen participation and the representation of diverse interests. However, Constitutional Court Decision Number 55/PUU-XVIII/2020 introduced significant changes to the political party verification process, creating differential treatment based on previous electoral performance. This article explores the implications of this decision on the integrity of Indonesia’s multiparty system and its broader democratic framework. Employing a normative legal research methodology, the study uses a qualitative-normative approach that incorporates statutory, conceptual, and comparative analyses. It also examines Constitutional Court Decision Number 62/PUU-XXII/2024 regarding the presidential threshold, reaffirming the importance of equal and fair electoral mechanisms for all political parties. Findings indicate that exempting certain parties from factual verification undermines the constitutional principle of equal treatment and risks reducing competitiveness and inclusivity in the political system. The research proposes coalition-building mechanisms as a potential solution to preserve political diversity while adhering to the electoral threshold requirements. This study contributes a novel perspective by integrating recent Constitutional Court decisions and critically analysing their effects on Indonesia’s evolving democratic structure. It further recommends future research to assess the broader impacts of such reforms and to draw comparative insights from other democracies with consistent and equitable party verification practices.